Przegląd wybranych badań nad moralnością podatkową. Wpływ moralności na rozmiary luk podatkowych - Kędrzyński, Adam (Annales. Etyka w Życiu Gospodarczym, 2020)
It is commonly stated that the behavioral aspect is problematic for economists. Nevertheless, a large strand of the literature on the topic exists, and it is high time we started making use of this fact. Using a simple literature review, the article presents some of the recent psychological discoveries from the fields of social psychology and behavioral economics that can be applied to macroeconomics in the context of estimating and reducing tax gaps (aim 1). Also, some fundamental methodological issues (aim 2a) and ethical distinctions between different meanings of procedural justice are raised (aim 2b).